Persistencies in the labour market - Paul Frijters; Maarten Lindeboom; Gerard J. van den Berg (Institute for the Study of Labor (IZA), 2009)
Using longitudinal income-tax registers, we study how past labour market outcomes affect current labour market transition rates. We focus on hysteresis effects of the durations and incidence of previous spells out of work. We estimate flexible multi-state Mixed Proportional Hazard specifications for transition rates between employment, unemployment, and welfare/non-participation. Our main finding is that after longer periods of employment with high income, individuals' transition rates from unemployment to employment increase. Longer periods of non-employment generally decrease future transition rates to work, and sometimes also from work. The quantitative magnitude of persistency and hysteresis effects on inequality is modest.
urn:nbn:de:101:1-20090306183
Keywords: J64; J22; C41; 330; Duration analysis; hysteresis; inequality; wages; unemployment; hazard rates; employment; income; work; Arbeitslosigkeit; Hysteresis; Berufliche Integration; Arbeitsmarkt; Statistische Bestandsanalyse; Niederlande